Understanding the adoption of multiple packages of system of rice intensification and its gender implications - Varma, Poornima (Indian Institute of Management, 2019)
Presented by Poornima Varma (Indian Institute of Management Ahmedabad), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.